New perspectives on sport and deviance : consumption, performativity, and social control - Blackshaw, Tony; Crabbe, Tim (Routledge, 2004)
The everyday makeup of contemporary sport is increasingly characterised by a perceived explosion of 'deviance' - violence, drug taking, racism, homophobia, misogyny, corruption and excess. Whereas once these behaviours may have been subject to the moral judgments of authority, in the face of dramatic socio-cultural change they become more a matter of populist consumer gaze. In addressing these developments this book provides a new and insightful approach toward the study of 'deviance' in the realm of sport. New Perspectives in Sport and 'Deviance'awakens the sociology of sport to the possibilities of re-imagining 'deviance' and offers an evocative approach which will appeal both to academics and students in the field of sociology of sport and sociology of deviance.